MENINGKATKAN KREATIFITAS GURU MENGAJAR MELALUI SUPERVISI AKADEMIK DENGAN TEKNIK KONSELING PERTEMUAN INDIVIDUAL - Abdul Rahmat; Zohra Maulana (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
This research was conducted as an evaluation on cooperative supervision by the principal in increasing teaching creativity at SMAN 1 Tolangohula in Gorontalo with research subject was 16 teachers. Based on the findings of the observation and data analysis a conclusion obtained that increasing of academic supervision by the principal through individualized counseling techniques has improved the quality of teaching creativity. Teacher should optimize their creativity in planning, learning implementation, and interpersonal relationships with students, because those types of creativity are very substantive elements in enhancing the teachers’ professionalism.